Effectiveness of Low-Intensity Extracorporeal Shock Wave Therapy in Erectile Dysfunction: An Analysis of Sexual Function and Penile Hardness at Erection: An Umbrella Review - Medrano-Sanchez, Esther; Pena-Cantonero, Belen; Candon-Ballester, Paloma; Blanco-Diaz, María; Díaz-Mohedo, Esther (MDPI, 2024)
The present umbrella review of five systematic reviews and meta-analyses was conducted to investigate the effectiveness of Low-Intensity Extracorporeal Shock Wave Therapy (Li-ESWT) in the treatment of vascular origin Erectile Dysfunction (ED). A search was carried out in the databases of Pubmed, Scopus, Medline, Scielo and Embase. Participants were divided into two groups: an experimental group receiving Li-ESWT and a control group receiving simulated shock waves. The main variable of this study is ED, measured using the International Index of Erectile Function-Erectile Function (IIEF-EF) and the Erection Hardness Score (EHS) scale. The results showed a statistically significant increase in the mean IIEF-EF score in the experimental group. Overall, four out of five articles reported an increase in the EHS score in the Li-ESWT group compared to the placebo. Concerning the treatment parameters, better outcomes were observed with an energy density of 0.09 mJ/mm2 and the application of 1500-2000 pulses. Additionally, a follow-up of 6-12 months resulted in greater improvement in ED compared to 3 months, although more studies investigating follow-ups beyond 12 months are needed. Obtaining conclusive and clear results is challenging; however, everything indicates that Li-ESWT is an innovative therapeutic alternative for vascular-origin ED due to its low risk and improvement in erectile function.
Keywords: Impotencia - Estudio de casos; Erectile dysfunction; Extracorporeal shock wave therapy